Studi Partisipasi Siswa Dalam Kegiatan OSIS Sebagai Pembelajaran Kewarganegaraan Di SMA Negeri 3 Mataram - Sri Ayu Esti Ningsih; Vivi Silvia Paramitha (Educational Note, 2025)
This study aims to examine student participation in Intra-School Student Organization (OSIS) activities as a form of civic education at SMA Negeri 3 Mataram. OSIS serves as a platform for character development and a means to actualize democratic values, responsibility, and social skills that are essential in shaping active and responsible citizens. The research employed a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The subjects of the study included OSIS board members, students actively involved in OSIS activities, OSIS supervising teachers, and the vice principal for student affairs. The findings indicate that student involvement in OSIS activities provides real-life experiences in practicing civic values such as leadership, decision-making, cooperation, and tolerance. OSIS activities also offer students opportunities to understand their rights and responsibilities as members of the school community, in line with the principles of civic education. However, it was found that the level of student participation is still influenced by individual motivation, school environment support, and understanding of OSIS's role as a medium for non-formal learning. Therefore, there is a need to strengthen the role of OSIS within the hidden curriculum to maximize the function of civic learning through active and sustainable student participation.